A national analysis of the outcome of major head and neck cancer surgery: implications for surgeon‐level data publication. (December 2013) - Nouraei, S.A.R.; Middleton, S.E.; Hudovsky, A.; Darzi, A.; Stewart, S.; Kaddour, H.; Alam, P.; Jallali, N.; Birchall, M.A.; Ghufoor, K.; Aylin, P.; Clarke, P.M.; et al.
<x xml:space="preserve">Abstract</x> Objectives To undertake a national outcomes analysis following major head and neck cancer surgery in order to identify risk factors for complications and in‐hospital mortality, as well as areas whose closer examination and formal benchmarking in the context of local and national quality assurance audits may lead to improved results for this condition. Design An analysis using Hospital Episode Statistics data. Settings All units undertaking major head and neck cancer surgery in England. Main outcome measures Cancer sites, co‐morbidities, social deprivation, surgical and non‐surgical treatments, complications, and in‐hospital mortality were recorded. Regression analysis was used for casemix adjustment and for identifying independent predictors of complications and mortality. Funnel plots were used for data visualisation. Results We identified 10 589 major head and neck cancer operations performed in England between 2006 and 2011. There were 7312 males, and mean age at surgery was 63 ± 13 years. Oral cavity (42%) and the larynx (28%) were the commonest cancer sites. At least one complication occurred in 33.1% of patients, and there were 322 (3.05%) in‐hospital deaths. Variables associated with in‐hospital mortality were trust volume, age, co‐morbidities, performing emergency major surgery and performing a tracheostomy or reconstructive surgery. Occurrence of major medical complications including pulmonary infections (7%), major acute cardiovascular events (4.7%) and acute renal failure (0.6%) also increased mortality risk. The analysis identified units that were outside of crude and risk‐adjusted 99.8% limits of confidence for complications and mortality. Conclusion Mortality following head and neck cancer surgery shows significant national variation and is associated with fixed risk factors like age and co‐morbidities, but also with modifiable risk factors like performing major surgery during an emergency admission, tracheostomy, reconstructive surgery and medical complications. We propose that the quality of tracheostomy care, reconstructive surgery, emergency major surgery rate, and occurrence and treatment of major medical complications should be closely examined and formally benchmarked as part of loco‐regional and national quality improvement audits.